KARAKTERISTIK ARESTER SEBAGAI PERLINDUNGAN PESAWAT TELEPON DARI SAMBARAN PETIR - , YOGI KRISNA BRIAN HUTAMA; , Prof. Dr. Ir. T. Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
On electronic equipment that is used as a means of telecommunication that uses the power supply of the distribution network will be susceptible to interference from lightning impuls voltage that induced on distribution networks, requiring lightning protection equipment such as installation of arrester. This research purposed to determine the effect of the increased voltage impulse against character of wave cuts as well as leakage current arrester characteristic both in new condition or after being hit by a bolt of lightning surge in efforts to protect the phone and internet modem network from induced voltages caused by lightning strikes. The research begins with knowing the leakage current of the arrester before hitted by impulse voltage is to know that the arrester is in good order. The basis of this test is to provide a nominal voltage started from 10 volts to 200 volts DC voltage, the next test arrester RJ-11 is hitted by impulse voltage with raising impulse test voltages peak ranging from 202.32 volt to 1225.16 volts. In the final test, repeatability test performed on the arrester leakage current to determine whether there is a change arrester leakage current characteristics after exposure to impulse. Based on the test results there is found no leakage current at arrester RJ11, both in new condition or after being charged with the impulse voltage. This is because the arrester using air insulation types (Gas Tube Arrester). Wave form of the cutting test results indicated that the arrester has the good work characteristics cause of able to deduct the value of the impulse voltage in a safe boundary for the protected electrical equipment in accordance with existing standards